2019
DOI: 10.32615/bp.2019.023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA319 family members play an important role in Solanum habrochaites and S. lycopersicum responses to chilling and heat stresses

Abstract: This is an open access article distributed under the terms of the Creative Commons BY-NC-ND Licence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…By means of transgenic approaches it was established 9 that miR167 acts as transcriptional regulator in response to bacterial infection (Jodder, Basak, Das & Kundu, 2017) and temperature-induced stress in tomato plants (Jodder et al, 2018). Multiple evidences obtained by both sRNA-sequencing and transgenic approaches, support the role of members of the miR319-family, an ancient miRNA conserved across plant species ranging from mosses to higher plants, as a key modulator of the plant-environment interrelation (at biotic and abiotic level) in monocotyledonous and dicotyledonous species (Bustamante et al, 2018;Liu et al, 2019;Shi et al, 2019;Wu, Qi, Meng & Jin, 2020;Fang et al, 2021;Joshi, Chauhan & Das, 2021). Finally, regarding miR398 and miR408 families, it was recently proposed that these conserved miRNAs, involved in the maintenance of the cooper homeostasis in plants, might be also involved in the systemic signaling of the response to biotic and abiotic stresses (Burkhead et al, 2009;Sanz-Carbonell, Marques, Martinez & Gomez, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…By means of transgenic approaches it was established 9 that miR167 acts as transcriptional regulator in response to bacterial infection (Jodder, Basak, Das & Kundu, 2017) and temperature-induced stress in tomato plants (Jodder et al, 2018). Multiple evidences obtained by both sRNA-sequencing and transgenic approaches, support the role of members of the miR319-family, an ancient miRNA conserved across plant species ranging from mosses to higher plants, as a key modulator of the plant-environment interrelation (at biotic and abiotic level) in monocotyledonous and dicotyledonous species (Bustamante et al, 2018;Liu et al, 2019;Shi et al, 2019;Wu, Qi, Meng & Jin, 2020;Fang et al, 2021;Joshi, Chauhan & Das, 2021). Finally, regarding miR398 and miR408 families, it was recently proposed that these conserved miRNAs, involved in the maintenance of the cooper homeostasis in plants, might be also involved in the systemic signaling of the response to biotic and abiotic stresses (Burkhead et al, 2009;Sanz-Carbonell, Marques, Martinez & Gomez, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…By means of transgenic approaches, it was established that miR167 acts as a transcriptional regulator in response to bacterial infection (Jodder et al, 2017) and temperatureinduced stress in tomato plants (Jodder et al, 2018). Multiple pieces of evidence obtained by both sRNA sequencing and transgenic approaches support the role of the members of the miR319 family, an ancient miRNA conserved across plant species ranging from mosses to higher plants, as a key modulator of the plant-environment interrelation (at biotic and abiotic levels) in monocotyledonous and dicotyledonous species (Bustamante et al, 2018;Liu et al, 2019;Shi et al, 2019;Wu et al, 2020;Fang et al, 2021;nee Joshi et al, 2021). Finally, regarding miR398 and miR408 families, it has been recently proposed that these conserved miRNAs involved in the maintenance of the cooper homeostasis in plants might be also involved in the systemic signaling of the response to biotic and abiotic stresses (Burkhead et al, 2009;Sanz-Carbonell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…miR319c-3p is involved in plant development and abiotic stress response ( Shi et al, 2019 ). The expression of miR319c-3p decreased in response to heat stress, whereas its expression increased in moderately chill-tolerant and sensitive tomato genotypes ( Shi et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…miR319c-3p is involved in plant development and abiotic stress response ( Shi et al, 2019 ). The expression of miR319c-3p decreased in response to heat stress, whereas its expression increased in moderately chill-tolerant and sensitive tomato genotypes ( Shi et al, 2019 ). This suggested that it may have been responsible for the up-regulation of the tosinte branched/ cycloidea/ proliferating cell factors genes ( TCP3 , TCP29 , and TCP2 ) ( Shi et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation